A Proposed Marketing Strategy For Furniture Business: The Case of Embet Furniture - Muhammad Haikal Mahdi; Novika Candra Astuti (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Embet Furniture is an Indonesian furniture company founded in 2000 and produces high-quality teak wood furniture through retail and online sales. The company offers a variety of products, including standard catalog furniture, custom furniture made from solid wood, HPL multiplex, and steel, as well as repair services. Throughout its operations, Embet Furniture has collaborated with various clients, including boutique hotels, architects, and interior design firms. However, the company faced challenges with below-target sales due to increased competition from imported products and a suboptimal digital marketing strategy. This study aims to analyze Embet Furniture's condition, evaluate its existing business model, and formulate a new marketing strategy. The external analysis included PESTEL, Porter's 5 Forces, and customer perceptions, while the internal analysis utilized STP, IRO, Business Model Canvas, and the Marketing Mix. The analysis results were used to assess and redevelop the business model, considering both internal and external factors. The new marketing strategy focused on increasing brand awareness, sales performance, and expanding the B2C and B2B segments through digital marketing optimization to support sustainable business growth